The Effect of Giving Cow Manure on the Productivity of Setaria Grass - Novita, Maulina; Ramdani, Dedi; Habiyah, Umul; Hidayat, Rahmat; Firli, Firli (Journal of Engineering Science and Technology Management, 2023)
Forage is the main feed for ruminant livestock. Before starting a ruminant livestock business, farmers need to plan the availability of forage before the ruminant livestock are brought to the livestock location. The main feed for ruminant livestock comes from consuming fresh forage ranging from 10-15% of the livestock's body weight. One of the superior grasses used as animal feed is setaria grass (Setaria sphacelata). Increasing the productivity of superior grass is influenced by several factors, including seeds, climate, weather, water and fertilizer. Manure is a product made from livestock waste that is given to agricultural land to improve soil fertility and structure. This research aims to determine the effect of giving cow manure on the growth of plant height, leaf width, leaf length, and the number of setaria grass saplings. Application of cow manure resulted in a significant increase in plant height, leaf length and fresh weight of setaria grass. The best results were found in the P2 treatment, namely by providing 300 grams of cow manure per planting hole.